Antagonismes. - Alvard, Julien; Read, Herbert; Salles, Georges; Palais du Louvre, Paris (Paris : Musée des Arts Decoratifs, 1960)
Agam, Yaacov ; Alechinsky, Pierre ; Alonso, Angel ; Appel, Karel ; Assar, Nasser ; Bacon, Francis ; Beauford-Delaney ; Bellegarde, Claude ; Benrath, Frédéric ; Bettencourt, Pierre ; Bogart, Bram ; Brô, René ; Brüning, Peter ; Bryen, Camille ; Burne-Jones, Edward ; Burri, Alberto ; Carpeaux, Jean-Baptiste ; Carrière, Eugène ; Chassériau, Théodore ; Compard, Emile ; Cuixart, Modest ; Dado ; Degottex, Jean ; Diaz de la Pena, Narcisse Virgie ; Domoto, Hisao ; Dubuffet, Jean ; Duque, Manuel ; Duvillier, René ; Ensor, James ; Fantin-Latour, Henri ; Fautrier, Jean ; Feito, Luis ; Ferron, Marcelle ; Flandrin, Jean-Hippolyte ; Fontana, Lucio ; Francis, Sam ; Garcia, Mario ; Gaul, Winfred ; Giacometti, Alberto ; Götz, K.O. (Karl Otto) ; Graziani, Piero ; Guitet, James ; Van Haardt, Georges ; Hantaï, Simon ; Hartung, Hans ; Hoehme, Gerhard ; Hultberg, John ; Hundertwasser ; Ionesco, Nicolas ; Jacquemon, Pierre ; Johannot, Tony ; Kalinowski, Horst Egon ; Kandinsky, Wassily ; Karskaya, Ida ; Kemeny, Zoltan ; Klein, Yves ; Kline, Franz ; Koenig, John-Franklin ; Koskas, Georges ; Kujaski, Jerzy ; Laubiès, René ; Lerin, Fernando ; Loubchansky, Marcelle ; Maeda, Josaku ; Masson, Andre ; Mathieu, Georges ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Matthews, Gene ; Messagier, Jean ; Michaux, Henri ; Millarès, Manuel ; Mitchell, Joan ; Moreau, Gustave ; Mortensens, Richard ; Nevelson, Louise ; Parc, Julio Le ; Pasternak, Leonid ; Prachensky, Markus ; Réquichot, Bernard ; Riopelle, Jean-Paul ; Roszda, Endre ; Rothko, Mark ; Sallès, Francis ; Schulze, Bernard ; Sonderborg, K.R.H. ; Soto, Jesus Rafael ; Soulages, Pierre ; Stubbing, Tony ; Tal-Coat, Pierre ; Tanaka, Flavio Shiro ; Tàpies, Antoni ; Ting, Wallace ; Tinguely, Jean ; Tobey, Mark ; etc.
geboortedata per kunstenaar
Frans
Antagonismes, Musée des Arts Decoratifs, Paris ; Palais du Louvre, Paris Février 19601960-02
boek